Online performance strategies for indie musicians during movement control order in Malaysia / Nur Munirah Shamsuddin - Shamsuddin, Nur Munirah (2022)
Since the announcement of the first Movement Control Order in Malaysia, Covid-19 become the main topic in news. At them time, Malaysia was having a total lockdown. Most of the economic sectors in Malaysia cannot run their operation. During MCO, all borders and interstate travelling were not allowed. 18* March 2020 was the first day Malaysia having lockdown. All sectors including music sector were affected by the virus. The musicians cannot continue their work to earn money. Hence, just to make ends meet, the musicians need to do everything that they can. There are several musician that sell product just to make a living. This include online concert or performances. Online concert already had been done by Korean artist such as NCT 127, BTS and Ateez. So, this prove that online concert/performances can be done. For this study, I will choose three artist indie musicians which are Bihzhu, Hujan and Meeia Too. Thus, their online performance will be study to determine the source of income for musicians during MCO. The online performance views and posting on their social media.